2019
DOI: 10.1042/bsr20190224
|View full text |Cite
|
Sign up to set email alerts
|

The enhanced immunological activity of Paulownia tomentosa flower polysaccharide on Newcastle disease vaccine in chicken

Abstract: The extracts of Paulownia tomentosa (P. tomentosa) exhibit multiple pharmacological activities. In the present study, P. tomentosa flower polysaccharides (PTFP) were extracted by water decoction and ethanol precipitation, and the immunologic modulations of PTFP against Newcastle disease (ND) vaccine was investigated in chickens. The results showed that in a certain range of concentrations, PTFP treatment can dose-dependently enhance lymphocyte proliferation. Then, 280 14-days-old chickens were randomly divided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…Numerous studies have demonstrated that polysaccharides extracted from Chinese medicinal herbs could enhance immune responses and promote the efficiency of vaccines by oral administration ( Xie et al, 2012;Feng et al, 2013;Tang et al, 2019;Zhang et al, 2020). In our previous study, PTFP, extracted from P. tomentosa flower, had been proved to possess the immunomodulatory activity and enhance immune responses for orally administered ND-vaccine in chickens (Yang et al, 2019). Wang et al (2019) have reported that PTFP as a new immunopotentiator or adjuvant could enhance humoral and cellular responses in chickens by injection administration.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Numerous studies have demonstrated that polysaccharides extracted from Chinese medicinal herbs could enhance immune responses and promote the efficiency of vaccines by oral administration ( Xie et al, 2012;Feng et al, 2013;Tang et al, 2019;Zhang et al, 2020). In our previous study, PTFP, extracted from P. tomentosa flower, had been proved to possess the immunomodulatory activity and enhance immune responses for orally administered ND-vaccine in chickens (Yang et al, 2019). Wang et al (2019) have reported that PTFP as a new immunopotentiator or adjuvant could enhance humoral and cellular responses in chickens by injection administration.…”
Section: Discussionmentioning
confidence: 98%
“…PTFP was prepared by water decoction and ethanol precipitation as previously described (Yang et al, 2019). In brief, dried cultured P. tomentosa flowers were extracted twice with boiling water for 2 hours and 1 hour, respectively.…”
Section: Preparation Of Ptfpmentioning
confidence: 99%
See 1 more Smart Citation
“…The first treatment was fed the basal diet only without any PLE supplementation (served as a control), while the second, third, and fourth treatments were fed on a basal diet supplemented with 0.1, 0.3, and 0.5 mg g/kg diet of PLE, respectively. The concentrations examined were selected based on the results of Yang et al ( 17 ).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the high-flavonoid concentration of paulownia elongate leaf extracts, both dried and fresh, suggests that this plant has the potential for novel therapeutic applications against a broad range of oxidative disorders ( 12 ). Therefore, paulownia leaves, fruits, and flowers (a wood by-product) are the most important plant parts employed in the folk herbal medicine ( 16 , 17 ). According to a Chinese medical book edited by Li Shizhen in 1578, paulownia bark might be applied to treat hemorrhoids and worms infections, while the flowers could be used to reduce swelling and promote hair development ( 16 ).…”
Section: Introductionmentioning
confidence: 99%